Factors that influence the clinical and technical success of venoplasty in patients with central venous stenosis at Saiful Anwar hospital - Kurnianingsih, Novi; Akbar, Akita Rukmana (Universitas Brawijaya, 2025)
Background: Central venous stenosis (CVS) is a common complication in long-term hemodialysis patients, particularly those with a history of central venous catheterization. Percutaneous transluminal venoplasty is the primary treatment modality; however, its success varies depending on anatomical and procedural factors. Objectives: This study aimed to evaluate the procedural success of venoplasty in CVS patients and to identify anatomical and procedural factors associated with wire-crossing failure and residual stenosis of less than 30%. Materials and Methods: A retrospective study was conducted involving 55 patients with CVS who underwent venoplasty at Dr. Saiful Anwar General Hospital, Malang, between 2021 and 2025. Data collected included patient demographics, lesion characteristics, and procedural variables. Data were analyzed using SPSS version 27. Descriptive statistics were used to summarize baseline characteristics. Chi-square or Fisher’s exact tests were used for bivariate analysis, followed by multivariate logistic regression to determine independent predictors of procedural success. Results: Wire crossing was successfully achieved in 76.4% of cases, while balloon venoplasty resulted in residual stenosis <30% in 74.5% of patients. Multivariate analysis revealed that total occlusion (OR 1.619; 95% CI: 1.243–2.109; p = 0.001), presence of venous collaterals (OR 1.429; 95% CI: 0.974–2.094; p = 0.048), and vessel tortuosity (OR 2.237; 95% CI: 1.258–3.978; p = 0.000) were significantly associated with wire-crossing failure. Clinical success (residual stenosis <30%) was significantly associated with non-total occlusion (OR 1.542; 95% CI: 1.164–2.043; p = 0.014) and absence of vessel tortuosity (OR 2.610; 95% CI: 1.362–5.001; p = 0.000). No significant associations were found between procedural outcomes and factors such as wire type, balloon pressure, or puncture technique. Conclusion: Anatomical characteristics—including total occlusion, vessel tortuosity, and collateral formation—are the key determinants of venoplasty success in patients with CVS, outweighing the influence of procedural variables. Comprehensive anatomical assessment prior to intervention is essential to optimize procedural outcomes.